Justifications for the Production of Functional Food Products Based on Local Raw Materials - Tukhtarov Bakhrom Eshnazarovich (Global Scientific Publishing, 2023)
One of the outstanding achievements of the end of the 20th century is the development of a fundamentally new concept of "probiotics and functional nutrition", affecting many fundamental and applied aspects of human health, medicine, nutrition and biotechnology [1-3]. The concept of functional nutrition is currently understood as such food products that, when included in the diet, provide the human body not so much with energy and plastic material as they control and modulate (optimize) specific physiological functions, biochemical and behavioral reactions, contribute to maintaining health, reduce the risk diseases and accelerate the healing process [4-6]. In recent decades, in Uzbekistan, as well as throughout the world, there has been an increased demand for high quality products with targeted properties. This phenomenon is connected, on the one hand, with the growth of the purchasing power of the population, and, on the other hand, with the desire to ensure health through harmless and healthy food products. Judging by the forecasts of the world's leading experts in the field of nutrition and medicine, in the next 15-20 years the share of functional food products will reach 30% of the entire food market. At the same time, they will displace many traditional medicines from the sales sphere by 35-50% [7-9].
Keywords: forecasts; purchasing; population